Large Auricular Chondrocutaneous Composite Graft for Nasal Alar and Columellar Reconstruction - Son, Daegu; Kwak, Minho; Yun, Sangho; Yeo, Hyeonjung; Kim, Junhyung; Han, Kihwan (Archives of Plastic Surgery, 2012)
Background Among the various methods for correcting nasal deformity, the composite graft is suitable for the inner and outer reconstruction of the nose in a single stage. In this article, we present our technique for reconstructing the ala and columella using the auricular chondrocutaneous composite graft.Methods From 2004 to 2011, 15 cases of alar and 2 cases of columellar reconstruction employing the chondrocutaneous composite graft were studied, all followed up for 3 to 24 months (average, 13.5 months). All of the patients were reviewed retrospectively for the demographics, graft size, selection of the donor site and outcomes including morbidity and complications.Results The reasons for the deformity were burn scar (n=7), traumatic scar (n=4), smallpox scar (n=4), basal cell carcinoma defect (n=1), and scar contracture (n=1) from implant induced infection. In 5 cases of nostril stricture and 6 cases of alar defect and notching, composite grafts from the helix were used (8.9×12.5 mm). In 4 cases of retracted ala, grafts from the posterior surface of the concha were matched (5×15 mm). For the reconstruction of the columella, we harvested the graft from the posterior scapha (9×13.5 mm). Except one case with partial necrosis and delayed healing due to smoking, the grafts were successful in all of the cases and there was no deformity of the donor site.Conclusions An alar and columellar defect can be reconstructed successfully with a relatively large composite graft without donor site morbidity. The selection of the donor site should be individualized according to the 3-dimensional configuration of the defect.
Keywords: Ear; Nose; Transplants